Corrosion of phosphorus bronze in different biodiesel blends and its remedial measures - Fazal, M.A.; Rathinee, B.; Masjuki, Haji Hassan (2016)
Biodiesel, as an alternative renewable fuel has some technical advantages over conventional petroleum diesel. However, it is more corrosive for automotive materials. The corrosion behaviour of phosphor bronze was studied through immersion test in B0 (diesel), B20 (20% biodiesel and 80% diesel), B50 (50% biodiesel and 50% diesel) and B100 (biodiesel) for 1440 hours. Similar test was carried out with the addition of additive Tert-butylamine and Benzotriazole in B20 and B100. The coupons were weighed before and after the immersion test to determine the weight loss and corrosion rate. The metal surface was characterized by Scanning Electron Microscopy and Energy Dispersive X-Ray (SEM/EDX), while fuels were analysed by measuring the Total Acid Number (TAN) and density. The results show that corrosiveness of biodiesel blend for phosphorous bronze increases with the increase of biodiesel concentration. The presence of additive Tert-butylamine and Benzotriazole retards the corrosion attack and protects the phosphorous bronze from deterioration. However, Benzotriazole was found to be more efficient and effective corrosion inhibitor for phosphor bronze in biodiesel.